PEMBELAJARAN & BELAJAR MEMBACA AL-QUR’AN DI TPA RIYADHUL MUBTADIIN - Fitri Nurbait; Matnur Ritonga (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2022)
The purpose of this study was to determine the use of the methods used in learning to read the Qur'an. There are 3 methods used, namely the Iqro method, private, and classical. The Iqro method is a method of reading the Qur’an which is directly related to reading practice. The Iqro method was compiled by Ustadz As'ad Human who is domiciled in Yogyakarta. Iqro 'book of 6 volumes plus 1 volume which contains prayers. In addition, the classical method is also used in learning the Qur’an here. The results of the Iqro method research can make it easier to learn the Qur’an.